Return to sports: A risky business? a systematic review with meta-analysis of risk factors for graft rupture following ACL reconstruction - Cronström, A.; Tengman, E.; Häger, C. K. (Sports Medicine, 2023)
Background: The risk of sustaining a graft rupture after anterior cruciate ligament reconstruction (ACLR) is high. Contributing risk factors are, however, still not clearly identified. Objective: The aim of this systematic review was to identify and quantify risk factors for graft rupture after ACLR. Methods: A systematic review with meta-analysis (PROSPERO CRD42020140129) based on PRISMA guidelines was performed. MEDLINE, CINAHL and EMBASE were searched from inception to September 2021. Prospective and retrospective studies addressing risk factors for graft rupture after ACLR in males/females of all ages were considered. Meta-analyses using a random effect model (effect measure: odds ratio [OR] with 95% confidence interval [CI]) were performed. The GRADE tool was used to assess evidence quality. Results: Following full-text screening of 310 relevant papers, 117 were eventually included, incorporating up to 133,000 individuals in each meta-analysis. Higher Tegner activity level (= 7 vs < 7) at primary injury (OR 3.91, 95% CI 1.69-9.04), increased tibial slope (degrees) (OR 2.21, 95% CI 1.26-3.86), lower psychological readiness to return to sport (RTS) (OR 2.18, 95% CI 1.32-3.61), early surgery (< 12 vs = 12 months) (OR 1.87, 95% CI 1.58-2.22), RTS (pre-injury level) (OR 1.87, 95% CI 1.21-2.91) and family history of ACL injury (OR 1.76, 95% CI 1.34-2.31) were all associated with increased odds of graft rupture. Higher age (OR 0.47, 95% CI 0.39-0.59), female sex (OR 0.88, 95% CI 0.79-0.98), fewer self-reported knee symptoms pre-reconstruction (OR 0.81, 95% CI 0.69-0.95) and concomitant cartilage injuries (OR 0.70, 95% CI 0.62-0.79) instead decreased the odds. Meta-analysis revealed no association between body mass index, smoking, joint laxity, RTS time, knee kinematics, muscle strength or hop performance and graft rupture. Conclusion: Conspicuous risk factors for graft rupture were mainly sports and hereditary related. Few studies investigated function-related modifiable factors or included sports exposure data.